EXPERIMENTAL STUDIES OF DEFORMATION AND STRENGTH INDICATORS OF LYOSS SOILS AT DIFFERENT HUMIDITY. - A.A.Koxorov (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
Compression experiments of lyoss soils of different humidity without structural damage, compression experiments with slow increase of moisture content of soil samples during the experiment, shear experiments of displacement of samples of ultra-sedimentary lyoss soils with unstable structure at different humidity.